Ethnomathematics: Rice Procession Faced with Batubara Malays of North Sumatra - Sonya Liani Nasution; Siti Salamah Br Ginting (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
This study aims to examine the cultural links in a local area with mathematical concepts or commonly known as ethnomathematics. This ethnomathematical research raises the topic of discussion about a "Nasi Face-to-face" procession at weddings in the traditional Malay culture of Batubara, North Sumatra. This research will explore what mathematical aspects are contained in a regional culture of the Batubara Malay tribe, especially the “Nasi Face-to-face” procession. Descriptive qualitative research method with ethnographic approach is used in this study. The results showed that in the procession of "Nasi Facing-front" found various mathematical concepts related, namely sets, functions, geometry of flat shapes, and geometry of geometric shapes. With this research, it is hoped that it can be used as a unique medium for learning mathematics as well as getting to know the local culture that is applied in learning mathematics in schools.